ANALISA YURIDIS TERHADAP SISTEM KAMERAL MAJELIS PERMUSYAWARATAN RAKYATSESUDAH PERUBAHAN UNDANG-UNDANG DASAR 1945 - Fernando Silalahi (to-ra, 2019)
Abstract In the life of a state that longs for a political justice, surely in the Basic Law or the Constitution in the country the inventor of his ideas and / or its founders have included a power sharing system that seeks to re ect political justice. If it must be connected with the form of the state, in fact this idea remains rooted in political justice. In the distribution of power, which according to John Locke is divided into legislative power, executive power, and judicial power, there must be authority that is balanced with each other and not overlapping. This was stated by John Locke so that power is not centralized within one institution, thereby reducing the risk of abuse and creating a democratic state. Keywords: political justice; legislative power; judicial power; democratic state.